Analisis Peran Na, K, Ca, dan Fe Terhadap Potensi Slagging dan Fouling pada Pembakaran Lignit, Sub-Bituminus, dan Ampas Tebu: Analisis Peran Na, K, Ca, dan Fe Terhadap Potensi Slagging dan Fouling pada Pembakaran Lignit, Sub-Bituminus, dan Ampas Tebu - Dhafin Umara; Shofa Rijalul Haq; Rizki Khoiriah Nasution; Ratna Mustika Dewi; Muhammad Faiz Shafiyurrahman (Chemistry Department, 2025)
Slagging and fouling are major operational challenges in coal and biomass combustion, often reducing thermal efficiency and shortening equipment lifespan. This study investigates the roles of sodium (Na), potassium (K), calcium (Ca), and iron (Fe) in influencing slagging and fouling tendencies across three fuel types: sub-bituminous coal, lignite, and sugarcane bagasse. Proximate, ultimate, and XRF analyses were used to derive several predictive indices, including the Base-to-Acid Ratio (B/A), Bed Agglomeration Index (BAI), Slag Viscosity Index (Sr), Fouling Index (Fu), Dolomite Ratio (Dol), and Simplified Base/Acid Ratio (B/As). The results indicate that Na and K play dominant roles in increasing fouling propensity, while Ca and Fe contribute to improving ash thermal stability. Sub-bituminous coal exhibits low slagging potential, lignite shows a high tendency, and sugarcane bagasse demonstrates intermediate behavior. These findings suggest that higher concentrations of basic oxides (CaO, Fe₂O₃) mitigate slagging risks, whereas elevated alkali oxides (Na₂O, K₂O) enhance fouling formation.